Pengaruh Kinerja Keuangan, Intellectual Capital, Financial Distress Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2020 - Latifa Harija (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
The research aimed to analyze the effect of financial performance, intellectual capital, financial distress, sales growth, and firm size on the firm value of the manufacturing companies listed on the Indonesia stock exchange in 2017-2020. The sample used in this research was 76 companies which were determined using the purposive sampling method. The data analysis techniques used are descriptive statistical analysis, multiple regression analysis, and hypothesis testing. The results of the research concluded current ratio and sales growth had a negative effect on the firm value, return on asset, financial distress, and firm size had a positive effect on firm value, debt to equity ratio, total asset turnover, and intellectual capital has no effect on firm value